2014
DOI: 10.1371/journal.pone.0085248
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Vasoactive Intestinal Peptide as a Prognostic Marker in Early Arthritis

Abstract: ObjectiveSuitable biomarkers are essential for the design of therapeutic strategies in personalized medicine. Vasoactive intestinal peptide (VIP) has demonstrated immunomodulatory properties in autoimmune murine and ex vivo human models. Our aim was to study serum levels of VIP during the follow-up of an early arthritis (EA) cohort and to analyze its value as a biomarker predicting severity and therapeutic requirements.MethodsData from 91 patients on an EA register were analyzed (76% rheumatoid arthritis (RA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 31 publications
(35 reference statements)
8
42
0
1
Order By: Relevance
“…In a recent elegant study, Sun et al described the beneficial role of VIP in UC patients. In agreement with data reported in several rheumatic diseases [245,275,276], they found that serum VIP levels are lower in UC patients than in healthy controls. The study provided evidence showing that VIP serum levels are lower in IgE + UC patients than that in IgE¯UC patients [268].…”
Section: Inflammatory Bowel Diseasesupporting
confidence: 91%
“…In a recent elegant study, Sun et al described the beneficial role of VIP in UC patients. In agreement with data reported in several rheumatic diseases [245,275,276], they found that serum VIP levels are lower in UC patients than in healthy controls. The study provided evidence showing that VIP serum levels are lower in IgE + UC patients than that in IgE¯UC patients [268].…”
Section: Inflammatory Bowel Diseasesupporting
confidence: 91%
“…The effect of VIP has been studied extensively in the immune system, and its function on innate and adaptive immunity has been demonstrated clearly, having a beneficial effect on the development of several autoimmune disorders in animal models and in patients with RA [19,20,[27][28][29][30][31][32]49]. Indeed, eRA patients who are unable to up-regulate VIP, present a worse clinical course despite receiving more intense treatment [33]. Its effect on Th1/Th2 balance has been examined in in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…In human RA, VIP is present in the microenvironment of the joints, and its therapeutic effects have been supported by several studies [20,[29][30][31][32]. Circulating VIP levels have been described as a prognostic biologic marker, predicting the evolution of eRA patients [33]. Moreover, recently, it has been described that the pattern expression of the VPAC receptors is altered in Th cells from eRA patients and that VIP can modulate their pathogenic profile [34].…”
Section: Introductionmentioning
confidence: 96%
“…VIP is one of the best-studied neuropeptides with anti-inflammatory and immunomodulatory actions in normal and pathological conditions (1,2,3). There are evidences that VIP may have therapeutic effects for human Rheumatoid arthritis and might be used as a prognostic marker for this disease (3,4). However, there are no deepen studies related to the expression pattern, cellular location, signalling pathways and functionality of its receptors (VPAC 1 and VPAC 2 ) during the activation of Th cells.…”
mentioning
confidence: 99%
“…Recently, using deep TCR profiling, new data supporting potential role of CD8+ T cells in AS have been published by our group and others [2,3]. Despite heterogeneous phenotype 24% of patients from combined cohort of AS and PsA fulfill both CASPAR and modified new-york criteria [4]. Also there is known tendency for axial disease in HLA-B*27+ PsA patients Objectives: Here we for the first time applied deep TCR profiling to study T cell repertoire of inflamed joints of patients with PsA, to characterise the similarity in clonal composition between patients in presence and absence of HLA-B*27…”
mentioning
confidence: 99%